Generation Z employees' construal of workplace leadership: an application of the repertory grid technique - Clinton, Caitlyn (Organisational Psychology, 2025)
This study explores how South African Generation Z (Gen Z) employees construe organisational leadership. The Repertory Grid Technique (RGT) was used as a part of structured interviews with sixteen Gen Z employees (N = 16). In addition to thematic analysis, Principal Component Analysis (PCA) is utilised to explore nuanced patterns in the data, going beyond qualitative insights. The PCA results illuminate a compelling trend: participants not only align their perceptions of an ideal leader with their personal leadership aspirations but also exhibit unique construal patterns, emphasising the diverse array of leadership preferences within Gen Z employees. In conjunction with the thematic analysis, the PCA plots visually depict the intricate relationships between participants' ideal leader, their desired leadership style, and their current leader. This visual representation enhances our understanding of the complex interplay between aspirations and real-world experiences in the realm of organisational leadership among South African Gen Z employees. Furthermore, six distinct categories and themes emerge from the data: communication, people, work, leadership, personal, and task orientation. These categories provide a detailed map of the qualities, values, and behaviours considered crucial by Gen Z in a leader, offering deeper insights beyond the PCA findings. This study contributes to the field of organisational leadership by shedding light on Gen Z's workplace experiences and leadership perceptions and extends its impact by incorporating the use of RGT. The nuanced insights gained from the PCA analysis complement and enrich the qualitative findings, underscoring the importance of integrating both approaches. This dual-method approach not only advances our understanding of Gen Z but also enhances the applicability of RGT in the South African and broader organisational psychology research context. The comprehensive insights garnered from this study extend beyond academia, offering practical and nuanced guidance for organisational leaders and managers seeking to engage and collaborate with their Gen Z workforce authentically.